Development of avatar for Olympic weightlifting as visual feedback for motor skills acquisition - Noriega, C. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
During the process of acquisition of motor skills, corrective instructions known as feedback, are provided by experts for athletes, these lead the athletes to an improvement of learning or improvement performance. The purpose of this study was to create an avatar to represent accurately the movement of the Hang Power Snatch (derivative of the Snatch, the most complex of Olympic weightlifting movements) in order to be used as visual feedback during the acquisition of motor skills.